Comparative Assessment of Blood Parameters Including RBC, Hb, PCV, Red Cell Indices, Serum Ferritin, and Salivary Candidal Growth in Female Patients with Iron Deficiency Anemia and Iron Deficiency - Asra Saba; Garlapati Komali; Deepti Shrivastava; Mohammed A. Alghafli; Faisal Maqbul Alazmi; Salman A. S. Aljudaya; Artak Heboyan; Kumar Chandan Srivastava (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: Iron deficiency anemia (IDA) is a microcytic-hypochromic anemia prevalent in African and South Asian countries including India. Along with systemic, it presents various oral manifestations that can be diagnosed in dental setups. Literature suggests that there is a state of iron deficiency before it manifests as anemia, which eventually creates an immunodeficient body state that predisposes to various opportunistic infections such as oral candidiasis. Objectives: The present study was designed to evaluate and compare various components of the blood picture including the hemoglobin (Hb%), red blood cell (RBC) count, RBC indices, hematocrit, peripheral blood smear and serum ferritin between iron deficiency (ID), IDA, and healthy subjects. The study also attempts to compare and assess the salivary samples of ID for Candida growth. Material and Methods: A total of 252 female patients of age groups ranging from 18 to 70 years were selected. The study consisted of three study groups, namely, Group A, IDA patients (clinical manifestations with pallor); Group B, ID patients (clinical manifestations without pallor); and Group C, age-matched healthy controls, with 84 in each group. The blood samples were collected to evaluate the hematological parameters including Hb%, RBC count, RBC indices, hematocrit, peripheral blood smear, and serum ferritin. Later, a saliva sample was collected from all study groups to assess the Candida growth. The obtained data were subjected to statistical analysis using SPSS version 20.0 software. Results: The results demonstrated that ID patients had normal blood parameters as healthy controls except for serum ferritin, while IDA patients had significantly (P < 0.001) lower hemoglobin, RBC count, and blood cell indices, specifically mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and hematocrit compared to ID and healthy controls. A significant finding is that like IDA patients, ID patients exhibited reduced serum ferritin levels. Contrary to the IDA group, only a small percentage of ID patients had Candida growth, although this was not statistically significant. Conclusion: Within the limitations of the current study, the results showed significantly reduced serum ferritin levels in ID, while other parameters were within the normal limits, and found tendency to develop Candida growth compared with the control subjects. Further studies are warranted to establish the association and causal relationship.